PRAKTEK DEMOKRASI DAN PARTISIPASI MASYARAKAT DALAM PEMILIHAN KEPALA DESA DI DESA BAJOMULYO KECAMATAN JUWANA KABUPATEN PATI - Septiani, Melinda; Santosa, Edi; ., Fitriyah (Journal of Politic and Government Studies, 2017)
The election of the village head is one of the democratic parties that are held in the regions that have the government. In the general election of village heads there are many fraudulent acts such as money politics that can affect the voice of either whether it is money or basic needs. Community participation as an option can vote in the form of votes and determine who will be elected head of the village in Pilkades directly. People who are ready in the elections whether they participate in voting or golput and whether they vote because of the influence of money politics.The method used in this study is quantitative analysis is by data collection techniques by means of observation, questionnaires and documents. Data analysis techniques used by researchers to the results obtained is by statistical instrument application SPSS. SPSS is useful to minimize errors in the calculation of data recapitulation that is present percentage so that the data obtained in valid. The results of this study indicate how the money politics that exist in the selection of Village Head Bajomulyo Juwana District Pati 2013 by way of validity, reliability, single table and cross table for the results obtained can be maximized.Furthermore, the hypothesis tested by partial t test obtained by the results of 1.990 which means to be a comparison of whether there is influence money politics on public participation in the election of Head of Bajomulyo Village 2013 that is with the results obtained at 1.556 and 1.582 which means t table is greater than t arithmetic the result is that there is no political influence of money on the participation of the people in choosing. And it is expected that village level institutions provide a lot of political learning to the public so that people know the danger of money politics.Keywords : Money Politics, Society Participation , Election of village head